1990
DOI: 10.1126/science.2237442
|View full text |Cite
|
Sign up to set email alerts
|

A Cytoplasmic Protein Inhibits the GTPase Activity of H-Ras in a Phospholipid-Dependent Manner

Abstract: A cytoplasmic protein has been identified that inhibits the guanosine triphosphatase (GTPase) activity of bacterially synthesized, cellular H-Ras protein. This GTPase inhibiting protein is able to counteract the activity of GTPase activating protein (GAP), which has been postulated to function as a negative regulator of Ras activity. The potential biological importance of the GTPase inhibiting protein is further supported by its interaction with lipids. Phospholipids produced in cells as a consequence of mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(56 citation statements)
references
References 21 publications
0
56
0
Order By: Relevance
“…Lipids and lipid metabolites such as PA, polyphosphoinositides, and arachidonic acid strongly inhibit the activity of the NF1 protein and, to a lesser extent, that of pl20GAP (4,35). There are also reports of a GTPase inhibitory protein that blocks the action of GAPs on p2lras and can be activated by DAGs and the lipids that inhibit GAPs (34). These lipids are unlikely to be important in PKC regulation of p2lras, because there is no evidence in T lymphocytes that PKC induces increases in cellular levels of lipid metabolites such as arachidonic acid or PA.…”
Section: Discussionmentioning
confidence: 98%
“…Lipids and lipid metabolites such as PA, polyphosphoinositides, and arachidonic acid strongly inhibit the activity of the NF1 protein and, to a lesser extent, that of pl20GAP (4,35). There are also reports of a GTPase inhibitory protein that blocks the action of GAPs on p2lras and can be activated by DAGs and the lipids that inhibit GAPs (34). These lipids are unlikely to be important in PKC regulation of p2lras, because there is no evidence in T lymphocytes that PKC induces increases in cellular levels of lipid metabolites such as arachidonic acid or PA.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, the generation of phosphatidic acid may be important. It has been suggested that PA or more likely a metabolite of PA inhibits the H-Ras GTPase inhibitory protein, GAP (40,44). Thus, the production of PA might enhance v-Src signals going through H-Ras, which has previously been implicated in v-Src signaling (36).…”
Section: Discussionmentioning
confidence: 99%
“…These lipid affinity columns have also been utilized to identify a second protein with the ability to alter the GTPase rate of Ras proteins (29 (3,16,21,22). Serum has been reported to stimulate the production of arachidonic acid in different cell types (8-12, 14, 15, 23).…”
Section: Discussionmentioning
confidence: 99%